50 studies every ophthalmologist should know - Penman, Alan D.; Crowder, Kimberly W.; Watkins, William M., Jr. (William Marvin), 1981- (New York : Oxford University Press, 2020)
'50 Studies Every Ophthalmologist Should Know' presents key studies that have shaped the practice of ophthalmology. Selected using a rigorous methodology, emphasis has been placed on landmark studies which have influenced current ophthalmology practice guidelines. This book is a must-read for ophthalmologists, especially those in training or preparing for board review, as well as anyone who wants to learn more about the data behind clinical practice.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on April 20, 2020).
Keywords: Ophthalmology -- Case studies